Cloning and expression analysis of OsSPL3 promoter in rice - ZENG Huiling; MO Zuyi; PU Qiaoxian; WANG Jiashu; FAN Kai; LI Zhaowei (浙江大学学报. 农业与生命科学版)
OsSPL transcription factor plays an important role in the development and stress response of rice (Oryza sativa) roots, leaves, floral organs, and ears. In this study, the OsSPL3 promoter was analyzed to explore the expression pattern of OsSPL3 transcription factor in rice and its response to drought stress. The Cis-acting elements in the OsSPL3 promoter region were analyzed by PLACE and Plant CARE online softwares, and the recombinant expression vector of OsSPL3 promoter and β-glucuronidase(GUS) gene was constructed, which was transformed into ZH11 rice callus, and positive transgenic plants were obtained by screening. The GUS expression activity of pOsSPL3-GUS transgenic plants and the expression patterns under drought stress and abscisic acid (ABA) treatments were detected. The results of promoter analysis showed that in addition to the necessary transcription initiation core elements and light-responsive elements, the OsSPL3 promoter region also included three MYB-involved drought-inducible elements, three gibberellin-responsive elements, two anaerobic induction essential elements, one low temperature response element, one endosperm expression regulatory element, one zein metabolism regulatory element and one meristem expression-related regulatory element. The results of GUS staining showed that the expression activity of GUS gene in young leaves, stem sheaths, coleoptiles and other young tissues was high, as well as in the vigorous growth parts of roots such as root cap, meristem zone, and elongation zone. In addition, the drought stress could significantly enhanced the GUS activity of transgenic rice leaves and roots. It shows that OsSPL3 transcription factor plays a regulatory role in the process of coleoptile growth, new leaf formation, root extension and stem sheath elongation after seed germination, and OsSPL3 transcription factor is also involved in the response process of rice drought stress.